The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/molecules27072209
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation Behavior and Acute Dietary Risk Assessment of Thiamethoxam and Its Metabolite Clothianidin on Spinach

Abstract: Thiamethoxam and its metabolite clothianidin residues pose a potential threat to human health. This study aims to investigate the residue behavior and acute dietary risk assessment of thiamethoxam and clothianidin on spinach. Thiamethoxam and clothianidin were extracted using a quick, easy, cheap, effective, rugged, safe (QuEChERS) method and analyzed using liquid chromatography-tandem mass spectrometry (LC-MS/MS). At spike levels from 0.01 to 5 mg kg−1, the average recoveries of both analytes were in the rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In general, children were considered to be the most vulnerable group because they were particularly susceptible to pesticide-related hazards [ 38 ]. As shown, the RQa values were almost negatively correlated with age, the RQa values were highest for 2-year-olds children in the range of 1.25–1.34%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, children were considered to be the most vulnerable group because they were particularly susceptible to pesticide-related hazards [ 38 ]. As shown, the RQa values were almost negatively correlated with age, the RQa values were highest for 2-year-olds children in the range of 1.25–1.34%.…”
Section: Resultsmentioning
confidence: 99%
“…UPLC-MS/MS is a powerful analytical technique that combines the separation cap bilities of liquid chromatography with the high sensitivity and selective mass analysis pabilities of triple quadrupole mass spectrometry. As a chromatographic identificati instrument, mass spectrometry has a fast speed, good separation and wide applicatio [38]. So, the residual level of myclobutanil in tomato was analyzed using UPLC-MS/M The instrument method was provided by Waters engineers.…”
Section: Instrument Analysismentioning
confidence: 99%
“…Reddy et al (2022) found that thiamethoxam at the recommended rate was safe for crops and the environment. Also, Yang et al (2022) reported that thiamethoxam was safe and suitable for spinach under field conditions.…”
Section: Residues and Dissipation Of Thiamethoxam In Tomato Leaves An...mentioning
confidence: 99%
“…They have the advantages of high insecticidal activity, broad insecticidal spectrum, high efficiency, low toxicity, and long duration, and are low toxic to many beneficial insects and bees and other nontarget insects, and are relatively safe for humans and mammals (Su et al, 2022; Yang et al, 2017). Their mode of action is mainly through the inhibition of cholinesterase in the insect's body to play an insecticidal role, resulting in the blockage of nerve conduction, and ultimately leading to the death of the insect (Yang et al, 2024).…”
Section: Introductionmentioning
confidence: 99%